Extending the Concept of Ethnocracy: Exploring the Debate in the Baltic Context - Timofey Agarin (Cosmopolitan Civil Societies: An Interdisciplinary Journal, 2016)
The advance of liberal understanding of democracy with its interest in and constrained ability to interfere with citizens’ identities made cases of ethnocracy rare over the past decades. Over the past 25 years, Baltic politics and societies have experienced considerable change, however, as I demonstrate, considerable debate persists around the issues central to the argument about ethnocracy in the region. In the context, when discussing the central role played by state institutions in negotiating conflicts between groups over access to scarce resources of the state, it is central to see minorities as being in both the inferior numerical position as well as in symbolically more disadvantageous place: If we see democratic politics for what they are as majoritarian politics, and if we see these as taking place in the context of state institutions designed to uphold the ethnic majority dominance, then any kind of liberal democratic politics would be a good candidate for ethnocracy.